Omnichannel Integration and Performance of Large-Scale Retail Stores in Nairobi City County, Kenya - Kanoga, Simon; Samuel, Maina; Reuben, Njuguna (European Scientific Journal, ESJ, 2025)
The changes in the retailing industry have led to the emergence of omnichannel retailing, which has disrupted conventional retailing. The general objective was to determine the effects of omnichannel retailing on the performance of large-scale stores. The specific objective of the study was to investigate the impact of omnichannel integration on the performance of large-scale retail stores in Nairobi, Kenya. This study was anchored on the Resource-Based View theory and the Unified Theory of Acceptance and Use of Technology. The study used a cross-sectional design using descriptive and explanatory research designs. The large-scale retail stores served as the unit of analysis, while the heads of the marketing, IT, finance, and operations departments served as the units of observation. The pilot testing was conducted on questionnaires before data collection. The reliability of the questionnaire was assessed using Cronbach alpha, and 0.7 level was considered reliable, where the variables in the study were higher than the cut-off. The hypothesis was tested, and conclusions were drawn using multiple linear regression. Content analysis was used to extract meaning and make inferences from qualitative data. For hypothesis testing, the study used P-values and a 5% significance level to assess significance. The finding indicated (p= 0.001 < 0.05) a significance level and coefficient of 0.772, implying that an increase in omnichannel integration, holding all other variables constant at zero, results in a 0.772 increase in the performance of large-scale retail stores. The results of this study showed that omnichannel integration significantly affects the performance of large retail stores.